Cartografia per le emergenze - Carlucci, Renzo; Cristini, BiancaMaria; Fasolo, Michele (GEOmedia, 2016)
Cartography during emergencies takes an incredibly strategic value of fundamental importance for saving lives. But after is then forgotten without implement what is classically defined benefit in peacetime to be ready in time of war. The reflections in this paper are derived from some of the experiences accumulated in the field in urgent technical rescue in emergency events that have allowed us to highlight the important role that geomatics plays in such situations.